KEEFEKTIFAN SELF ASSESSMENT DAN PEER ASSESSMENT TERHADAP PENINGKATAN HASIL BELAJAR AKUNTANSI RANAH PSIKOMOTOR SISWA SMK - Rotingah, Titi; ., Sudiyanto; Muchsini, Binti (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objective of this research are to investigate: (1) difference in effectiveness of self assessment and teacher assessment towards improvement in psychomotor domain of accounting learning outcomes students and (2) difference in effectiveness of peer assessment and teacher assessment towards improvement in psychomotor domain of accounting learning outcomes students. This research using Quasi Experimental Design with the Nonequivalent Control Group Design. The results of research show that there is a difference in effectiveness of self assessment and teacher assessment towards improvement in psychomotor domain of accounting learning outcomes students. This can be seen from the value of Sig. (2-tailed) <Î± (0,010 <0,05). In addition, there is also differences in effectiveness of peer assessment and teacher assessment towards improvement in psychomotor domain of accounting learning outcomes students. This can be seen from the value of Sig. (2-tailed) <Î± (0,000 <0,05).Keywords: self assessment, peer assessment, accounting learning outcomes, psychomotor domainABSTRAKTujuan penelitian ini adalah untuk (1) menguji perbedaan keefektifan self assessment dan teacher assessment terhadap peningkatan hasil belajar akuntansi ranah psikomotor siswa dan (2) menguji perbedaan keefektifan peer assessment dan teacher assessment terhadap peningkatan hasil belajar akuntansi ranah psikomotor siswa. Penelitian ini menggunakan Quasi Experimental Design bentuk None-quivalent Control Group Design. Hasil penelitian menunjukkan bahwa terdapat perbedaan keefektifan self assessment dan teacher assessment terhadap peningkatan hasil belajar akuntansi ranah psikomotor siswa. Hal ini dapat dilihat dari nilai Sig.(2-tailed)<Î± (0,010<0,05). Selain itu, terdapat pula perbedaan keefektifan peer assessment dan teacher assessment terhadap peningkatan hasil belajar akuntansi ranah psikomotor siswa. Hal ini dapat dilihat dari nilai Sig.(2-tailed)<Î± (0,000<0,05).Kata Kunci: self assessment, peer assessment, hasil belajar akuntansi, ranah psikomotor